Management of the cervico‐petrous internal carotid artery in class C tympanojugular paragangliomas. Issue 6 (28th November 2015) - Bacciu, Andrea; Prasad, Sampath Chandra; Sist, Natalie; Rossi, Giulia; Piazza, Paolo; Sanna, Mario
Abstract: Background: Management of the cervical and petrous internal carotid artery (ICA) is frequently required in Fisch class C tympanojugular paragangliomas (TJPs). The purpose of this study was to discuss the perioperative intervention of the ICA in patients who underwent surgical resection of a TJP. Methods: A retrospective study of 237 patients surgically treated for Fisch class C TJPs was done to identify cases that required ICA management. Results: Management of the ICA was required in 176 patients (74.2%). Forty‐two patients required just an ICA decompression, 88 underwent a subperiosteal dissection, 19 underwent subadventitial dissection without intraluminal stenting, 17 underwent subadventitial dissection with intraluminal stenting, and 12 underwent arterial resection after permanent balloon occlusion. There were no complications associated with the endovascular procedures. Gross total tumor resection was achieved in 91.5% of the cases. Conclusion: Preoperative endovascular intervention, in selected cases, facilitates gross total tumor removal and significantly reduces the risk of an intraoperative ICA injury. © 2015 Wiley Periodicals, Inc. Head Neck 38: 899–905, 2016